Large-eddy simulation of gas–liquid two-phase flow in a bubble column reactor using a modified sub-grid scale model with the consideration of bubble-eddy interaction - Long, Shanshan; Yang, Jie; Huang, Xiaobing; Li, Guang; Shi, Weibin; Sommerfeld, Martin; Yang, Xiaogang (2020)
The Eulerian–Eulerian Large-eddy simulations (LES) of gas–liquid two-phase flow in a cylindrical bubble column reactor have been conducted. When considering the turbulent eddy viscosity in LES, apart from the well-accepted contributions from shear turbulence and bubble induced turbulence (BIT), the effect of the interaction between entrained bubbles and eddies with a similar turbulence length scale to the sub-grid scale (SGS) cannot be neglected. With the consideration of the bubble response to the eddies on the induced sub-grid stresses, a modified SGS model, which incorporates the Stokes number, St, was proposed. The results of LES clearly indicate that the use of the modified SGS model can effectively capture the transient bubbly flow in the cylindrical bubble column. The power turbulent kinetic energy spectrum obtained in LES indicates that a slope similar to Komogorov -5/3 scaling law and the -3 scaling law can still be identified for a critical frequency f=10.70 Hz. © 2020 The Author(s)